To the gods of war: Early Iron Age weapon hoards in the hinterland of Caput Adriae - Guštin Mitja; Božič Dragan (Arheološki vestnik, 2021)
Over four centuries at least, the abyss of Mušja jama near Škocjan in the Kras region of south-western Slovenia was the place where bronze weapons, protective warrior equipment, vessels and other objects were being deposited as part of prehistoric cult rituals. When these rituals ceased, a series of special iron weapon hoards, of the Tržišče-Porpetto type, appeared in the hinterland of Caput Adriae that largely consisted of spearheads. We can distinguish between the early and the late group of such hoards that differ in composition and distribution. The hoards of the early group, known in Istria, the Kras and Notranjska, consist of a small number of bronze spear- heads and axes, as well as iron weapons comprising short swords with a curved blade – machairas – alongside spearheads and axes. Two of the hoards also included a helmet and three horse bits. This group is dated between the late 8th and the mid-6th century BC. The late group has been recorded in the Posočje and Friuli regions. They revealed no bronze weapons and iron mach- airas, but rather new forms of iron weaponry (one-sided winged axes, shaft-hole axe, iron dagger) and horse equipment (bit with iron U-shaped cheek-pieces). They were buried in the second half of the 6th and in the 4th century BC.